Pelatihan Perawatan Luka Dikubitus Bagi Penyandang Disabilitas Di Posyandu Disabilitas Satu Hati - Esri Rusminingsih; Chori Elsera; Endang Sawitri; Marwanti Marwanti (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Neurological deficits due to trauma, stroke and physical disability cause patients to be bedridden or use a wheelchair for a long time. Bed rest and/or fixed body positions for long periods increase the risk of decubitus ulcers. Prevention efforts can be carried out with optimal nutritional support, reducing friction, pressure, pulling, making regular position changes and decubitus wound care. Most people with disabilities at Posyandu Satu Hati have decubitus wounds in the buttocks area, and have received wound care sets, but have never been trained in decubitus wound care. The aim of the activity was to improve the knowledge and skills of cadres and people with disabilities in decubitus care at Posyandu Satu Hati Disability Center, Klaten. The targets of this activity were cadres, families and clients with disabilities who had decubitus ulcers at Posyandu Satu Hati, Wedi District, Klaten Regency with a total of 30 participants. Interventions included decubitus care training and technical demonstration of decubitus wound care. The activity was attended by 30 participants, with an average age of 46.7 ± 14.1 years, mostly male 53.3%, most participants came from clients with disabilities (53.3%). The mean level of knowledge before training was 61.50 ± 8.69, and the level of knowledge after training was 94.70 ± 4.33. There was a significant increase in the level of knowledge of participants about the prevention and care of decubitus after training (p=0.001). During the training, all participants were enthusiastic in participating in the activities, there was an increase in participants' knowledge in the prevention and care of decubitus wounds, 8 participants actively asked questions.